2017
DOI: 10.1242/dev.157917
|View full text |Cite|
|
Sign up to set email alerts
|

Rho differentially regulates the Hippo pathway by modulating the interaction between Amot and Nf2 in the blastocyst

Abstract: The Hippo pathway modulates the transcriptional activity of Yap to regulate the differentiation of the inner cell mass (ICM) and the trophectoderm (TE) in blastocysts. Yet how Hippo signaling is differentially regulated in ICM and TE cells is poorly understood. Through an inhibitor/activator screen, we have identified Rho as a negative regulator of Hippo in TE cells, and PKA as a positive regulator of Hippo in ICM cells. We further elucidated a novel mechanism by which Rho suppresses Hippo, distinct from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…Several direct and indirect targets of ROCK1/2 kinases in the early embryo have been described ( Alarcon and Marikawa, 2018 ; Shi et al, 2017 ). Among these is YAP1, a transcriptional partner of TEAD4 ( Nishioka et al, 2009 ), since ROCK activity is required for the nuclear localization of YAP1 ( Kono et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several direct and indirect targets of ROCK1/2 kinases in the early embryo have been described ( Alarcon and Marikawa, 2018 ; Shi et al, 2017 ). Among these is YAP1, a transcriptional partner of TEAD4 ( Nishioka et al, 2009 ), since ROCK activity is required for the nuclear localization of YAP1 ( Kono et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cells then undergo asymmetric divisions that produce polarised and unpolarised cells, which will specify the TE or ICM lineages, respectively (Anani et al, 2014). The apical domain in polarised TE cells promotes YAP activity by sequestering Amot away from the basolateral domain, where it promotes activity of the core kinase cascade along with Nf2 (Cockburn et al, 2013;Hirate et al, 2015;Shi et al, 2017) and binds to YAP to limit nuclear import (Leung and Zernicka-Goetz, 2013). Polar cells also have higher cortical tension (Maître et al, 2016), and the change in Amot localisation could be mediated through an increase in F-actin at the apical domain (Anani et al, 2014;Leung and Zernicka-Goetz, 2013).…”
Section: The Role Of Yki/yap/taz In Regulating Cell Fatementioning
confidence: 99%
“…Several studies have also shown that Rho and Rho-associated coiled-coil kinases 1 and 2 (ROCK1 and ROCK2) are necessary for lineage formation by negatively regulating the Hippo pathway ( Kono et al , 2014 ; Shi et al , 2017 ; Alarcon and Marikawa, 2018 ). ROCK is activated by Rho small GTPases and then it phosphorylates a variety of targets involved in modulation of cellular processes such as cell polarity and gene expression ( Amano et al , 2010 ; Julian and Olson, 2014 ).…”
Section: Cellular and Molecular Mechanisms That Regulate Hippo Signalmentioning
confidence: 99%